Exploring Impacts of Integrating a Rehabilitation Dog into Physiotherapy from the Perspectives of Children with Cerebral Palsy and Their Caregivers. - Caron, Valerie; Oates, Alison; Petrin, Julie; Pinto, Romany; Lanovaz, Joel; Oosman, Sarah; Dell, Colleen A.; Donkers, Sarah (NeuroRehabilitation, 2025)
Background: Rehabilitation for children with cerebral palsy (CP) often includes physiotherapy to enhance community participation and quality of life. Animal-assisted services (AAS) are a novel approach in physiotherapy to increase motivation, enjoyment and wellbeing. Our team conducted a study integrating a rehabilitation dog (Loki) into animal-assisted physiotherapy (AA-PT) for children with CP. This study presents the experiences and perspectives of children with CP who worked with Loki. Methods: Interpretive Description approach with reflective thematic analysis was used. Semi-structured interviews were completed at two timepoints: T1) single timepoint walking with Loki; T2) after an 8-week AA-PT intervention with Loki (subset of participants). Results: Ambulatory children with CP aged 7–16 years (n = 11 (T1); n = 4 (T2)) and their caregiver (n = 11 (T1); n = 4 (T2)) participated. Three themes describing the perceived impact of working with Loki were described: 1) Connection, Relationship and Bonding; 2) Being upheld: physical support and emotional safety; 3) Empowerment Through Participation and Confidence. Conclusion: Children with CP and their caregivers reported immense enjoyment and value in having Loki present as part of the physiotherapy intervention. Centered around an immediate bond formed with Loki, the emotional and physical support children experienced improved willingness to participate in the AA-PT and in community following interactions with Loki.